2021
DOI: 10.1017/dmp.2021.166
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis on Road Traffic Collision Occurrence in Nigeria

Abstract: Objectives: Road traffic collisions (RTC) result in a significant number of preventable deaths worldwide. In 2010, the United Nations General Assembly launched, “The Decade of Action for Road Safety (2011–2020)” with the stated goal to “reduce road traffic deaths and injuries by 50% by 2020.” This study aims to analyze trends in RTC numbers and subsequent deaths with respect to road safety laws in Nigeria and to suggest suitable interventions. Methods: Annual reports for the period 2007–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…There was same change trends of motor vehicle traffic fatality rates in urban, rural, males and females, and the death rate of MVAs was at its peak in 2013. The trend of total mortality was similar with that of road traffic collisions in Nigeria ( Awoniyi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 72%
“…There was same change trends of motor vehicle traffic fatality rates in urban, rural, males and females, and the death rate of MVAs was at its peak in 2013. The trend of total mortality was similar with that of road traffic collisions in Nigeria ( Awoniyi et al, 2021 ).…”
Section: Discussionsupporting
confidence: 72%
“…Reviewing the yearly reports of road accidents in Nigeria from 2007-2017, we find that disobedience of traffic laws, loss of control, and reckless driving are the most common causes of road accidents there [3]. Previous studies have revealed that Nigerians know quite a bit about what might cause road traffic accidents, showing that the Federal Road Safety Corps (FRSC) is doing an excellent job of educating the public about how to keep themselves and others safe on the roads [4,3]. However, irrespective of this awareness, prevention of deaths on the roads (obeying the rules and attending to emergencies) may be linked more to the willingness to engage in prosocial behaviour anchored on personality [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Road accidents have become a regular and re-occurring phenomenon in Nigeria, constituting a menace in modern times, particularly in Ebonyi State [1,2]. Reviewing the yearly reports of road accidents in Nigeria from 2007-2017, we find that disobedience of traffic laws, loss of control, and reckless driving are the most common causes of road accidents there [3]. Previous studies have revealed that Nigerians know quite a bit about what might cause road traffic accidents, showing that the Federal Road Safety Corps (FRSC) is doing an excellent job of educating the public about how to keep themselves and others safe on the roads [4,3].…”
Section: Introductionmentioning
confidence: 99%